Aerobic Assessment - Sleivert, G.
"Aerobic fitness" is perhaps the most common of all fitness attributes evaluated in athletes. Endurance athletes rely on high levels of aerobic fitness since their rate of energy supply, or pace, is ultimately determined by their ability to convert fuels into ATP in the presence of oxygen. Athletes involved in intermittent anaerobic sports such as netball, rugby and hockey must also have well developed aerobic systems since recovery from anaerobic efforts is largely an aerobic process. The concept of aerobic fitness is somewhat vague however since their are several facets of aerobic energy supply important to the athlete. These include aerobic power, anaerobic threshold and economy of movement. Aerobic power, best measured directly in the athlete by determining maximal rate of oxygen consumption (VO2max), is the single best measure of an athletes maximum ability to take in oxygen from the air, load it into the blood, and transport it to the working muscles to sustain exercise aerobically. It therefore represents our best measure of the current aerobic training status of the cardio-respiratory system. Anaerobic threshold is a controversial term that is generally agreed to represent an exercise intensity above which energy supply become increasingly reliant on oxygen independent glycolysis or anaerobic metabolism. Exercise above anaerobic threshold intensity cannot be sustained for long due to the accumulation of metabolites such as lactic acid that contribute to fatigue. Economy of movement is particularly important for endurance athletes that must move as fast as possible for the least amount of energy expenditure. An economical athlete will have a lower oxygen consumption (VO2) at a given exercise intensity than a less economical athlete and will therefore be able to save energy for the later stages of a race or exercise harder for a similar energy expenditure.